Identification and estimation of multinomial choice models with latent special covariates - Nail Kashaev (The University of Western Ontario, Department of Economics, 2022)
Identification of multinomial choice models is often established by using special covariates that have full support. This paper shows how these identification results can be extended to a large class of multinomial choice models when all covariates are bounded. I also provide a new Ín-consistent asymptotically normal estimator of the finite-dimensional parameters of the model.
Keywords: C50; C57; 330; Multinomial choice; random coefficients; special covariate; identificationat infinity; bundles